Selenium recovery method based on copper anode slime

By using graphene mixed with concentrated sulfuric acid for roasting and spray tower treatment, the problem of low selenium recovery efficiency in copper anode mud was solved, achieving high-efficiency selenium recovery while maintaining the recovery efficiency of copper, silver, and gold.

CN121292378APending Publication Date: 2026-01-09WUXI YAOXIN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511387643.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-26
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

In existing technologies, the selenium recovery efficiency from copper anode slime is not high, especially since some selenium elements are difficult to be effectively distilled out during the sulfation roasting process, resulting in insufficient recovery efficiency.

Method used

A copper anode sludge was calcined by mixing graphene with concentrated sulfuric acid. The sludge was then subjected to high-temperature calcination under an inert atmosphere and spray treatment in a spray tower. The high conductivity and thermal stability of graphene were used to improve electron transport efficiency, causing selenium to be oxidized to SeO2 and reduced to elemental selenium. Combined with subsequent displacement reactions and reduction steps, efficient selenium recovery was achieved.

Benefits of technology

It significantly improved the recovery efficiency of selenium while maintaining the recovery levels of copper, silver, and gold. The introduction of graphene did not affect the recovery of other target components.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the field of recycling of refined copper byproducts, and particularly relates to a selenium recovery method based on copper anode slime, which comprises the following steps: oxidizing selenium element in barrel anode slime into SeO2 through concentrated sulfuric acid, steaming the SeO2 into a spray tower, contacting the SeO2 with spray water, converting the SeO2 into seleninic acid, reducing the selenium into elemental selenium by SO2 which is steamed, and settling the elemental selenium; meanwhile, the graphene is mixed and dispersed in reactants, and based on the structural stability of the graphene under high-temperature roasting, the promotion effect on electron transmission is reserved at the high temperature, so that the electron transfer efficiency of the redox reaction between the concentrated sulfuric acid and the anode slime can be improved, and the recovery rate of the anode slime is improved. Therefore, the conversion evaporation recovery efficiency of selenium in the anode slime is improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of refining copper by-product recycling, and particularly relates to a selenium recovery method based on copper anode slime. BACKGROUND

[0002] The anode in electrolytic refining is a crude metal (such as crude copper, etc.), and in addition to the main metal, the anode also contains a small amount or trace amount of other metal or non-metal element impurities, which exist in the anode in the form of an element, an alloy or a compound. In the process of electrolytic dissolution of the anode, these impurities are gradually dissolved out, and then adhere to the surface of the anode, or precipitate at the bottom of the electrolytic cell by gravity, or suspend in the electrolyte to form anode slime. These anode slimes often contain precious metals and certain rare elements, and thus have high recycling value. For example, the value of gold and silver in the anode slime produced by copper electrolytic refining is enough to offset the processing cost of the entire process of electrolytic refining.

[0003] The process of comprehensively recovering selenium, copper, gold, silver and other valuable components from copper anode slime is the post-treatment of copper anode slime, which is an important part of the modern copper electrolytic refining process. In many post-treatment operations, first, a sulfuric acid roasting selenium evaporation process is used. The anode slime is mixed with concentrated sulfuric acid and then subjected to high-temperature roasting reaction. The selenium element in the anode slime is evaporated in the form of SeO2 and then input into an adsorption tower to be sprayed with water to form selenite. Based on SO2 in the flue gas, the selenite is reduced to elemental selenium, thereby achieving recovery. However, in this process, a small part of the selenium element in the anode slime is not so easy to evaporate, so there is room for further improvement in the recovery efficiency of selenium. SUMMARY

[0004] To solve the above technical problems, the present application provides a selenium recovery method based on copper anode slime, which comprises the following steps (1):

[0005] The dry copper anode slime, concentrated sulfuric acid and graphene are mixed and stirred fully according to a mass ratio of 100:100-150:1-20, and then subjected to continuous roasting at 500-600°C in an inert atmosphere for 3-6 hours. During the roasting process, the generated flue gas is continuously transferred to a spray tower for spray treatment. Finally, the collected material at the bottom of the spray tower is filtered and separated to obtain a filtrate and a filter cake. The filter cake is dried to obtain recovered selenium.

[0006] At the roasting temperature, the concentrated sulfuric acid oxidizes the selenium element (including elemental selenium and selenium metal salt) in the anode slime into SeO2, which is evaporated with the flue gas into the spray tower, and then reduced to elemental selenium by SO2 in the flue gas while being converted into selenite by contact with the spray water, thereby completing the recovery of selenium. The main reaction formula is:

[0007] Se+2H2SO4→SeO2↑+2H2O+2SO2↑

[0008] CuSe + 4H2SO4→ SeO2↑ + CuSO4 + 3SO2↑ + 4H2O

[0009] Ag2Se + 4H2SO4→ SeO2↑ + Ag2SO4 + 3SO2↑ + 4H2O

[0010] Cu + 2H2SO4→ CuSO4 + 2H2O + SO2↑

[0011] 2Ag + 2H2SO4→ Ag2SO4 + 2H2O + SO2↑

[0012] SeO2 + H2O → H2SeO3

[0013] H2SeO3 + 2SO2 + H2O → Se↓ + 2H2SO4.

[0014] Meanwhile, graphene has high thermal stability and electrical conductivity, and after being fully mixed and dispersed in the reactants, the electron transfer efficiency of the redox reaction between concentrated sulfuric acid and anode sludge can be improved based on the promotion of electron transmission by graphene, thereby improving the conversion and evaporation recovery efficiency of selenium in the anode sludge.

[0015] And unlike other conductive materials, the hexagonal honeycomb lattice structure formed by carbon atoms in graphene can maintain high structural stability at high calcination temperatures with the protection of an inert atmosphere, so it retains good electrical conductivity for electron transmission at high temperatures. Unlike other conductive materials (such as metals), which can severely hinder the directional movement of electrons due to increased atomic vibration at high temperatures, resulting in almost complete loss of electrical conductivity.

[0016] Among them, concentrated sulfuric acid is a 98% mass fraction of sulfuric acid aqueous solution (the same below), the mixing and stirring between copper anode sludge, concentrated sulfuric acid and graphene is carried out in the slurry tank, calcination is carried out in a muffle furnace, and the gas-liquid ratio of the inlet gas during the spraying treatment is 1:10-1:5. The spraying liquid (water) is significantly higher in volume flow than the inlet gas volume flow of the flue gas, which helps to fully intercept selenium dioxide and soluble salts in the flue gas.

[0017] As a preferred: further comprising step (2):

[0018] Add the slag left after roasting in step (1) to water at a solid-liquid ratio of 1:3 to 10, and add concentrated sulfuric acid at a mass ratio of 20 to 30 to 100 with copper anode mud, sodium chloride at a mass ratio of 10 to 20 to 100 with copper anode mud, and the filtrate obtained by filtering and separating the collected material in step (1). After fully reacting at 60°C to 90°C under stirring, filter to obtain filtrate and precipitate. Then add elemental iron to the filtrate obtained in this step to carry out a displacement reaction to displace crude copper.

[0019] The concentrated sulfuric acid added in step (2) dissolves and leaches the metal oxides (such as copper oxide) in the slag after dilution. At the same time, the introduction of chloride ions causes the silver ions in the dispersion system to fully precipitate (the silver sulfate Ag2SO4 obtained from the reaction with concentrated sulfuric acid in step (1) and present in the slag is slightly soluble in water, while the introduced chloride ions combine with a small amount of silver ions dissolved in the water to form completely insoluble silver chloride AgCl, which precipitates first. Then, the previously undissolved Ag2SO4 begins to dissolve and release silver ions, which continue to be combined with chloride ions and precipitate. This process continues until the Ag2SO4 in the system is completely dissolved and converted into AgCl, thereby fully fixing the silver component in the anode mud in solid form). Thus, it is separated in the filtration operation in step (2), so that when the filtrate is replaced with elemental iron, elemental copper with higher purity can be recovered. The main reaction formula is:

[0020] Ag + +C1 — →AgC1↓

[0021] CuSO4 + Fe → FeSO4 + Cu↓.

[0022] As a preferred option, step (3) is also included:

[0023] The precipitate obtained by filtration in step (2) is added to water at a solid-liquid ratio of 1:2 to 8. Sodium chlorate, concentrated sulfuric acid, and sodium chloride are added to the water at a mass ratio of 1 to 1.5:100 with the copper anode mud, 2 to 5:100 with the copper anode mud, and 4 to 8:100 with the copper anode mud. The mixture is heated to 80°C to 90°C under stirring to fully leach and react. Then, solid-liquid separation is performed, and the separated liquid is collected.

[0024] In step (3), a strong oxidizing agent combined with acidic conditions is used to react and dissolve the previously stable and insoluble precious metal Au, thereby achieving the separation of gold Au from silver chloride AgCl precipitate and other insoluble substances. The main reaction formula is as follows:

[0025] 2Au+8HCl+NaC1O3→2HAuCl4+NaC1+3H2O.

[0026] Furthermore: it also includes step (4):

[0027] SO2 is introduced into the separation solution obtained in step (3) to reduce elemental gold, thus completing the recovery of gold. The main reaction formula is:

[0028] 2HAuCl4+3SO2+6H2O→3H2SO4+8HC1+2Au↓.

[0029] Furthermore, it also includes step (5):

[0030] The solid separated in step (3) is added to water at a solid-liquid ratio of 1:2 to 5, and ammonia is added (at a mass ratio of NH3 to copper anode mud of 6 to 12:100). The mixture is heated to 50°C to 70°C under stirring and allowed to react fully. The mixture is then filtered and the separated liquid is retained.

[0031] The purpose of this operation is similar to step (3) above: to dissolve the silver chloride AgCl complex in the solid, thereby separating the silver chloride AgCl from other insoluble substances (including the graphene specifically added in step (1)), and then recovering the silver by adding hydrazine hydrate to the separation liquid to reduce elemental silver. The main reaction formula is:

[0032] AgCl + 2NH3 → [Ag(NH3)2] + +C1 —

[0033] 4[Ag(NH3)2] + +NH₂NH₂+4OH — →N2↑+4Ag↓+4H2O+8NH3. Detailed Implementation

[0034] Example 1

[0035] (1) 730 kg of dried copper anode mud (containing relatively high amounts of selenium (approximately 15%), silver (approximately 26%), gold (approximately 4%), and copper (approximately 20%), 950 kg of 98% sulfuric acid aqueous solution, and 50 kg of graphene were mechanically stirred and mixed thoroughly in a slurry tank. The mixture was then transferred to a muffle furnace and roasted at 550°C for 4 hours under continuous argon gas supply. During the roasting process, the argon gas was continuously used as the carrier gas to carry the flue gas generated during roasting into a spray tower and sprayed at a gas-liquid ratio of 1:8 (volume ratio, the same below). After roasting and spraying were completed, the collected material at the bottom of the spray tower was filtered to obtain filtrate and filter cake. The filter cake was dried thoroughly to complete the recovery of selenium.

[0036] The weight after weighing was 106.7 kg. After analysis, its purity was 96.9%, so the total amount of selenium recovered can be calculated to be 103.4 kg.

[0037] (2) The slag left after roasting in step (1) is added to water at a solid-liquid ratio of 1:9 (mass ratio, the same below), and 150 kg of 98% sulfuric acid aqueous solution, 110 kg of sodium chloride, and the filtrate obtained from filtering the collected material in step (1) are added. The mixture is heated to 80°C under stirring and reacted for 1 hour. The filtrate and precipitate are then filtered. 115 kg of iron powder is added to the filtrate obtained in this step to carry out a displacement reaction, thereby completing the recovery of copper.

[0038] The weight after weighing was 140.8 kg. After analysis, its purity was 88.8%, so the total amount of copper recovered can be calculated to be 125 kg.

[0039] (3) Add the precipitate obtained by filtration in step (2) to water at a solid-liquid ratio of 1:6, and add 9 kg of sodium chlorate, 30 kg of sulfuric acid aqueous solution with a solute mass fraction of 98% and 40 kg of sodium chloride. After stirring, heat to 90°C and continue to react for 3 hours, then perform solid-liquid separation and collect the separated liquid.

[0040] (4) SO2 is fully introduced into the separation liquid obtained in step (3) to reduce elemental gold, and the elemental gold is filtered out and dried to complete the recovery of gold.

[0041] The weight after weighing was 28.5 kg. After analysis, its purity was 99.6%, so the total amount of gold recovered can be calculated to be 28.4 kg.

[0042] (5) Add the solid separated in step (3) to water at a solid-liquid ratio of 1:5. Add 250 kg of ammonia water with a mass concentration of 25%. Heat the mixture to 50°C under stirring and continue the reaction for 2 hours. Filter the mixture and retain the separated liquid. Reduce the silver in the separated liquid with hydrazine hydrate. After filtering out the elemental silver, dry it to complete the recovery of silver.

[0043] The weight after weighing was 195.3 kg. After analysis, its purity was 94.1%, so the total amount of silver recovered can be calculated to be 183.8 kg.

[0044] Example 2

[0045] (1) One ton of dried copper anode mud (from the same batch as the copper anode mud in Example 1), 1420 kg of 98% sulfuric acid aqueous solution, and 80 kg of graphene were mechanically stirred and mixed thoroughly in a slurry tank. Then, the mixture was transferred to a muffle furnace and calcined at 550°C for 4 hours under continuous argon gas supply. During the calcination process, the calcination flue gas was continuously carried into a spray tower using the introduced argon gas as the carrier gas and sprayed at an inlet gas-liquid ratio of 1:9. After both the calcination and spraying processes were completed, the collected material at the bottom of the spray tower was filtered to obtain filtrate and filter cake. After the filter cake was dried thoroughly, the selenium recovery was completed.

[0046] The weight after weighing was 148.4 kg. After analysis, its purity was 96.1%, so the total amount of selenium recovered can be calculated to be 142.6 kg.

[0047] (2) The slag left after roasting in step (1) is added to water at a solid-liquid ratio of 1:7. 200 kg of 98% sulfuric acid aqueous solution, 150 kg of sodium chloride, and the filtrate obtained from filtering the collected material in step (1) are added to the solution. The mixture is heated to 80°C under stirring and reacted for 1.5 hours. The filtrate and precipitate are then filtered. 150 kg of iron powder is added to the filtrate obtained in this step to carry out a displacement reaction, thereby completing the recovery of copper.

[0048] The weight after weighing was 186.5 kg. After analysis, its purity was 92.7%, so the total amount of copper recovered can be calculated to be 172.9 kg.

[0049] (3) Add the precipitate obtained by filtration in step (2) to water at a solid-liquid ratio of 1:6, and add 15 kg of sodium chlorate, 45 kg of sulfuric acid aqueous solution with a solute mass fraction of 98% and 60 kg of sodium chloride. After stirring, heat to 90°C and continue to react for 3 hours, then perform solid-liquid separation and collect the separated liquid.

[0050] (4) SO2 is fully introduced into the separation liquid obtained in step (3) to reduce elemental gold, and the elemental gold is filtered out and dried to complete the recovery of gold.

[0051] The weight after weighing was 37.8 kg. After analysis, its purity was 99.3%, so the total amount of gold recovered can be calculated to be 37.5 kg.

[0052] (5) Add the solid separated in step (3) to water at a solid-liquid ratio of 1:6, add 320 kg of ammonia water with a mass concentration of 25%, heat to 50°C under stirring and continue the reaction for 3 hours, filter and separate, retain the separated liquid, and reduce the silver in the separated liquid with hydrazine hydrate, filter out the elemental silver and dry it, thus completing the recovery of silver.

[0053] The weight after weighing was 276.0 kg. After analysis, its purity was 93.7%, so the total amount of silver recovered can be calculated to be 258.6 kg.

[0054] Comparative Examples

[0055] No graphene was added; all other components and procedures were the same as in Example 1.

[0056] (1) 730 kg of dried copper anode mud (from the same batch as the copper anode mud in Example 1) and 950 kg of 98% sulfuric acid aqueous solution were mechanically stirred and mixed thoroughly in a slurry tank. Then, the mixture was transferred to a muffle furnace and roasted at 550°C for 4 hours under continuous argon gas supply. During the roasting process, the argon gas was continuously used as the carrier gas to carry the flue gas generated during roasting into a spray tower and sprayed at an inlet gas-liquid ratio of 1:8. After roasting and spraying were completed, the collected material at the bottom of the spray tower was filtered to obtain filtrate and filter cake. After the filter cake was dried thoroughly, the selenium recovery was completed.

[0057] The weight after weighing was 92.4 kg. After analysis, its purity was 97.5%, so the total amount of selenium recovered can be calculated to be 90 kg.

[0058] (2) The slag left after roasting in step (1) is added to water at a solid-liquid ratio of 1:9. 150 kg of 98% sulfuric acid aqueous solution, 110 kg of sodium chloride, and the filtrate obtained from filtering the collected material in step (1) are added to the solution. The mixture is heated to 80°C under stirring and reacted for 1 hour. The filtrate and precipitate are then filtered. 115 kg of iron powder is added to the filtrate obtained in this step to carry out a displacement reaction, thereby completing the recovery of copper.

[0059] The weight after weighing was 143.6 kg. After analysis, its purity was 85.8%, so the total amount of copper recovered can be calculated to be 123.2 kg.

[0060] (3) Add the precipitate obtained by filtration in step (2) to water at a solid-liquid ratio of 1:6, and add 9 kg of sodium chlorate, 30 kg of sulfuric acid aqueous solution with a solute mass fraction of 98% and 40 kg of sodium chloride. After stirring, heat to 90°C and continue to react for 3 hours, then perform solid-liquid separation and collect the separated liquid.

[0061] (4) SO2 is fully introduced into the separation liquid obtained in step (3) to reduce elemental gold, and the elemental gold is filtered out and dried to complete the recovery of gold.

[0062] The weight after weighing was 27.9 kg. After analysis, its purity was 99.8%, so the total amount of gold recovered can be calculated to be 27.8 kg.

[0063] (5) Add the solid separated in step (3) to water at a solid-liquid ratio of 1:5. Add 250 kg of ammonia water with a mass concentration of 25%. Heat the mixture to 50°C under stirring and continue the reaction for 2 hours. Filter the mixture and retain the separated liquid. Reduce the silver in the separated liquid with hydrazine hydrate. After filtering out the elemental silver, dry it to complete the recovery of silver.

[0064] The weight after weighing was 192.4 kg. After analysis, its purity was 97.3%, so the total amount of silver recovered can be calculated to be 187.2 kg.

[0065] The above weighing analysis results show that, compared to the control example, in Example 1, while maintaining the same recovery levels of copper, silver, and gold, the selenium recovery efficiency was significantly improved. This is because selenium recovery in this scheme relies on sulfation roasting. The introduction of graphene effectively increases the electron transport conductivity path in the raw materials during sulfation roasting, thereby improving the electron transfer efficiency of the redox reaction between concentrated sulfuric acid and anode mud, i.e., the efficiency of this chemical reaction, and thus promoting the efficiency of selenium distillation. When excess reactants were subsequently added to recover copper, silver, and gold, the recovery levels of copper, silver, and gold remained the same as in Example 1 and the control example. This also indicates that the introduction of graphene in this scheme does not affect the recovery of the remaining target components in the anode mud.

Claims

1. A method for selenium recovery based on copper anode slime, characterized in that, Including step (1): Dry copper anode mud, concentrated sulfuric acid, and graphene are mixed and stirred thoroughly at a mass ratio of 100:100-150:1-20. The mixture is then heated to 500℃-600℃ in an inert atmosphere and continuously calcined for 3-6 hours. During the calcination process, the generated flue gas is continuously transferred to a spray tower for spray treatment. Finally, the collected material at the bottom of the spray tower is filtered to obtain filtrate and filter cake. The filter cake is dried to obtain recovered selenium.

2. The selenium recovery method based on copper anode mud as described in claim 1, characterized in that: The air-liquid ratio of the spray treatment is 1:10 to 1:

5.

3. The selenium recovery method based on copper anode mud as described in claim 1, characterized in that, It also includes step (2): After adding the slag left after roasting in step (1) to water at a solid-liquid ratio of 1:3 to 10, concentrated sulfuric acid with a mass ratio of 20 to 30 to 100 to the copper anode mud, sodium chloride with a mass ratio of 10 to 20 to 100 to the copper anode mud, and the filtrate obtained by filtering and separating the collected material in step (1) are added. The mixture is then heated to 60°C to 90°C under stirring to react fully. After filtration, the filtrate and precipitate are obtained. Elemental iron is then added to the filtrate obtained in this step to carry out a displacement reaction to displace crude elemental copper.

4. The selenium recovery method based on copper anode mud as described in claim 3, characterized in that, It also includes step (3): The precipitate obtained by filtration in step (2) is added to water at a solid-liquid ratio of 1:2 to 8. Sodium chlorate, concentrated sulfuric acid, and sodium chloride are added to the water at a mass ratio of 1 to 1.5:100 with respect to the copper anode mud, respectively. The mixture is heated to 80°C to 90°C under stirring to fully leach and react. Solid-liquid separation is then performed, and the separated liquid is collected.

5. The selenium recovery method based on copper anode mud as described in claim 4, characterized in that: SO2 is introduced into the separation liquid obtained in step (3) to reduce elemental gold.

6. The selenium recovery method based on copper anode mud as described in claim 4, characterized in that: The solid obtained from the solid-liquid separation in step (3) is added to water at a solid-liquid ratio of 1:2 to 5, and ammonia is added to it. After the mixture is heated to 50°C to 70°C under stirring and fully reacted, it is filtered and separated, and the separated liquid is retained. Elemental silver is reduced by adding hydrazine hydrate to the separated liquid obtained in this step.

7. The selenium recovery method based on copper anode mud as described in claim 6, characterized in that: The ammonia water is added according to the mass ratio of NH3 to the copper anode mud of 6-12:100.